2016
DOI: 10.1155/2016/2507973
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Optical Quality between Small Incision Lenticule Extraction and Femtosecond Laser LASIK

Abstract: Purpose. To investigate the visual quality after SMILE and Femto-LASIK. Methods. About 123 eyes from 63 patients were enrolled in this study. The parameters were measured preoperatively and 1 week, 1 month, and 3 months postoperatively using Sirius System. Results. The MTF curve increase slightly from low to high frequency at 3 mm and 6 mm pupil diameter after SMILE surgery (P < 0.05) during the follow-up time comparing with the preoperative values. And the SR has a significant increase at various pupil diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Many clinical studies have evaluated the pre- and post-operative effect on straylight after refractive surgery. The results were consistent: post-operative straylight values in myopes after laser-assisted in situ keratomileusis (LASIK)/ laser-assisted epithelial keratomileusis (LASEK)1014 or after phakic intraocular lens (pIOL) implantation15,16 were on average slightly lower than pre-operative straylight measurements. Assumptions were made that these improvements are the result of ill-tolerated contact lenses pre-operatively 13,15,16.…”
Section: Introductionsupporting
confidence: 52%
“…Many clinical studies have evaluated the pre- and post-operative effect on straylight after refractive surgery. The results were consistent: post-operative straylight values in myopes after laser-assisted in situ keratomileusis (LASIK)/ laser-assisted epithelial keratomileusis (LASEK)1014 or after phakic intraocular lens (pIOL) implantation15,16 were on average slightly lower than pre-operative straylight measurements. Assumptions were made that these improvements are the result of ill-tolerated contact lenses pre-operatively 13,15,16.…”
Section: Introductionsupporting
confidence: 52%
“…Additionally, a recent prospective clinical study, which included 123 eyes of 63 patients in China (mean preoperative MRSE ± SD: −5.55 ± 1.23 D), demonstrated that in the early postoperative phase up to 3 months, even though both techniques showed great improvement in optical quality at a small pupil diameter, SMILE showed better optical quality than FS-LASIK in eyes with larger pupil diameters, which may lead to better night vision with the SMILE procedure than with LASIK. [20].…”
Section: Resultsmentioning
confidence: 99%
“…The current study found no significant differences in postoperative UDVA and CDVA between the SMILE and LASIK groups, which is consistent with several previous reports. 15 , 18 20 However, Ganesh and Gupta 21 reported that their SMILE group achieved a higher rate of UCVA (20/20 or better) than the LASIK group. In our study, all patients in both groups achieved UDVA and CDVA 20/20 or better at 3 months after surgery.…”
Section: Discussionmentioning
confidence: 99%